The evolution of Pharmaceutical Care in medication dispensing in the brazilian context (Research, Society and Development, 2025)
The present article aims to describe, through a literature review, the importance of pharmaceutical care in the medication dispensing process and, specifically, to discuss the advances in this practice, highlighting the competencies required for safe and effective dispensing. Pharmaceutical care in medication dispensing remains a central component of health actions in Brazil and has undergone important conceptual and operational advances in recent years. Current evidence demonstrates the growing recognition of the pharmacist’s role in promoting the safe, effective, and rational use of medicines, especially in Primary Health Care and community pharmacies. Despite these advances, significant challenges still persist, such as insufficient training focused on patient-centered care, high service demand, structural limitations in many health units, and fragmented communication among multiprofessional teams. Vulnerable populations—including older adults, patients with chronic diseases, and users with low health literacy—remain exposed to risks related to inappropriate medication use, reinforcing the need for continuous pharmaceutical interventions. Overall, the literature shows that although important progress has been made, the implementation of pharmaceutical care in dispensing still occurs heterogeneously across the country. These findings highlight the importance of strengthening professional competencies, improving service organization, and incorporating evidence-based strategies that ensure safe dispensing and more effective therapeutic outcomes.